Short-term impacts of pomace application and Pseudomonas bacteria on soil available phosphorus. (September 2020) - Ghorbanzadeh, N.; Mahsefat, M.; Farhangi, M.B.; Khalili Rad, M.; Proietti, P.
Abstract: This study was conducted with the aim of investigating phosphorus release from pomace or solid olive waste in the presence of phosphorus solubilizing Pseudomonas bacteria. A multi-level factorial experiment with complete randomized design was employed in three replications. A calcareous soil was mixed with 2 and 4 g pomace per 100 g soil (W2 and W4, respectively) and inoculated with indicator and soil isolated Pseudomonas sp. (10 6 cell g −1 ) (Pf and Pi, respectively). Soil without pomace and Pseudomonads were also included as control (W0Pn). Mixtures incubated in sterile and non-sterile conditions for 4 months. Sampling was carried out at 0, 2, 7, 14, 28, 42, 56, 86 and 120 days and some soil biochemical properties were measured. The effects of pomace, bacteria, incubation time and their interactions were significant on pH, EC, basal respiration, organic carbon (OC), available phosphorus (Pava ) and phosphatase activity ( p ≤ 0.01). Pomace increased soil OC content in both non-sterile and sterile conditions. The maximum amount of Pava in non-sterile mixtures was observed in W4Pi (133.25 mg kg −1 ). Pomace and phosphorus solubilizing bacteria addition to soil increased phosphatase activity. Although Pava concentration was highest in W4 treatments during the incubation period, its trend was ascending in W2 treatments. It seems that 2 g pomace per 100 g soil is enough for improving biological properties and phosphorus availability. Overall, the application of pomace with P-solubilizing bacteria can be a solution to increase soil available P level, reduce dependency on chemical P fertilizers and sustainable management of such solid wastes. Highlights: We evaluated the role of pomace and Pseudomonas bacteria on soil available phosphorus. Pomace (0, 2 and 4%) and Pseudomonas bacteria were applied to soil. Sterile and non-sterile soil-pomace mixtures incubated for 4 months. Pomace addition and Pseudomonas inoculation enhanced soil available phosphorus. The maximum Pava level was observed in 4% pomace and isolated Pseudomonas .